New perspectives on civic engagement as outcome of higher education: an exploratory case study - van den Wijngaard, Oscar; Beausaert, Simon; Gijselaers, Wim; Segers, Mien (Frontline Learning Research, 2024)
This study explores the potential of a new perspective on research into the impact higher education has on the civic engagement of students. We propose a shift from viewing engagement itself as the key dependent variable to two ‘fundamental constituents’, political interest and agency. Both constituents have been presented as either static or determined entirely by factors external to education such as maturation, but also as dynamic and affected by various aspects of the educational experience in higher education. Furthermore, as analyses of these effects based on sample means do not account sufficiently for the intersectionality of background variables that define the student experience, we propose that data are explored through cluster analysis. Employing this type of analysis, a case study conducted at a small international liberal arts college in the Netherlands showed four distinctly different patterns in the development of both constituents of civic engagement. Based on further data obtained from the same sample, we offer suggestions for specific foci in further research about the impact of higher education on the development of civic engagement.